2004
DOI: 10.1007/s00405-004-0816-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of virus infection as a cause of Meniere?s disease or endolymphatic hydrops assessed by electrocochleography

Abstract: Meniere's disease (MD) may follow viral infection such as by neurotropic viruses known to invade the endolymphatic sac (ES) and provoke endolymphatic hydrops (EH). The objective of this study was to investigate whether neurotropic viruses may cause infection of the inner ear and provoke EH. Antiviral immunoglobulin (IgG) assay against herpes simplex 1 (HSV1), herpes simplex 2 (HSV2), adenovirus (ADV), varicella zoster virus (VZV) and cytomegalovirus (CMV) were performed in 109 patients with an advanced stage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…Among these insults, immune-mediated responses in the inner ear end organs, such as the endolymphatic sac, stria vascularis, and spiral ligament, are thought to be the main bases for the fluid homeostatic disorder in MD (30,31). Certain virus infections, such as varicella-zoster, EpsteinBarr, and adenovirus infections, of the endolymphatic sac in early childhood represent other bases for the dysfunction of endolymph absorption (32,33). Taken together with the present data, it is suggested that autoimmune responses and/or virus infections could modify the V2R regulatory system in the endolymphatic sac, resulting in V2R overexpression there (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Among these insults, immune-mediated responses in the inner ear end organs, such as the endolymphatic sac, stria vascularis, and spiral ligament, are thought to be the main bases for the fluid homeostatic disorder in MD (30,31). Certain virus infections, such as varicella-zoster, EpsteinBarr, and adenovirus infections, of the endolymphatic sac in early childhood represent other bases for the dysfunction of endolymph absorption (32,33). Taken together with the present data, it is suggested that autoimmune responses and/or virus infections could modify the V2R regulatory system in the endolymphatic sac, resulting in V2R overexpression there (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This number includes a total of 919 etiologic and pathologic studies. Many different causes of Mé-nière's disease have been proposed, such as an anomaly or variant vestibular aqueduct [11][12][13] , local autoimmune disorder [14][15][16][17] , viral infection [19] , water metabolic disorder [18] , and gene mutation [20][21][22] ; however, the exact cause remains unknown. Although we cannot rule out the possibility that Ménière's disease is a hydrops complex of 11.7% 88.3% -n = Number of audiogram pairs; recovery = shift to a milder category; worsening = shift to a more severe category.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators interested in the disease have looked at endolymphatic sac pathology [8][9][10] , morphology of the vestibular aqueduct [11][12][13] , local allergy and immunology [14][15][16][17] , water metabolism [18] , viral infection [19] , and gene mutation [20][21][22] . It is quite striking that causes of the disease and effective therapies are still unknown despite the vast number of experimental and clinical studies conducted over the past half century.…”
Section: Introductionmentioning
confidence: 99%
“…Ear infections caused by adenovirus infection are generally restricted to the middle ear (Heikkinen, 2000;Monobe et al, 2003), although evidence of inner ear infection in Meniere's disease and AIDS exists (Davis et al, 1995;Selmani et al, 2005). It is unclear whether adenovirus produces pathology in these instances, but it remains an important consideration as significant attention is being given to adenovirus as a vector for inner ear gene transfer (Davis et al, 1995;Izumikawa et al, 2005).…”
Section: Introductionmentioning
confidence: 98%